Strategic Management of Powdery Mildew of Grapes Using Fungicides and Bio-Control Agents - Saha, Sujoy; Thosar, Ratna U.; Das, Dimpi; Chavan, Vijayashree (International Journal of Bio-resource and Stress Management, 2023)
The study was carried out at ICAR-NRCG, Pune, Maharashtra, India during November–February of 2019–2020 and 2020–2021 to evaluate the bio-efficacy of fungicides and biocontrol agents and level of tolerance against powdery mildew of grapes. Total 18 treatments categorised into three groups were taken into account. Three groups viz. fungicides, biocontrol agents (Bacillus licheniformis, Trichoderma afroharzianum, Ampelomyces quisqualis) along with metrafenone and commercial formulations of biocontrol agents were analysed for disease control. A total of five applications of each treatment were made during the growing season. Results showed that, in case of Group I (registered fungicides), Hexaconazole 5 EC @ 1 ml l-1/ Difenoconazole 25 EC @ 0.5 ml l-1/Myclobutanil 10 WP @ 0.4 g l-1/Two sprays of sulphur @ 2 g l-1 was most effective in controlling the disease. In case of pure culture, Trichoderma afroharzanium had proved to be most effective in the control of powdery mildew when sprayed in alteration with Metrafenone. In Group III, alternate applications of commercial formulations of Bacillus subtilis (2 ml l-1), Trichoderma viridae (2 g l-1), Ampelomyces quisqualis (5 ml l-1) and sulphur (2 g l-1) was most effective in controlling the disease. It was concluded that the application of bio-control agents in alternation with chemical fungicides controlled the disease effectively.